Benefit of Wardah Innovation Through the Colourverse Program in Creating Skin Tone Harmony - Jessica Julia Markus; Naila Rushad; Rudy Harjanto (Communicare : Journal of Communication Studies, 2026)
The rapid growth of Indonesia’s beauty industry has been accompanied by increasing interest in self-care and personalized beauty. However, limited consumer understanding of skin tone and undertone often leads to unsuitable cosmetic choices. This creates an opportunity for beauty brands to combine consumer education, personalization, and technological innovation. This study examines Wardah’s Colourverse initiative using a qualitative case analysis. Keller’s brand equity theory and Rogers’ Diffusion of Innovations theory are applied to analyze how AI-based personalization contributes to consumer education, brand perception, and technology adoption. Colourverse uses AI-powered facial scanning to analyze skin tone, undertone, and lighting conditions and recommend suitable cosmetic shades. The initiative provides consumers with an interactive and educational experience that supports more informed product selection while encouraging appreciation of individual skin characteristics. It also strengthens perceptions of Wardah as an innovative and consumer-oriented local beauty brand. The findings suggest that AI-based beauty personalization can function beyond product recommendation as a strategic branding and educational tool. Colourverse demonstrates how technological innovation may strengthen brand differentiation, consumer engagement, and the adoption of personalized beauty solutions in Indonesia’s competitive cosmetics market.